Effect of Informative Videos on Knowledge Gain of the Wheat Growers - Nisha, Nisha; Sharma, Anil; Tiwari, Devinder (Indian Journal of Extension Education, 2021)
A study was conducted during the year of 2019 in Ludhiana district of Punjab to assess the impact ofÂ informative videos on gain in knowledge of respondents related to recommended wheat productionÂ technologies. A multi-stage sampling procedure was followed, a quasi-experimental pre and posttest, and control group was selected. The experimental group was exposed to the informative videos on wheat productionÂ technologies whereas no treatment was given to the control group. Three stages contact was made i.e., before treatment, at the time of treatment (video exposure) and after treatment to know the gain in knowledge. TheÂ findings of the study showed that a positive and significant difference between before and after exposure to the informative videos (t = 10.2, p < 0.05) whereas the control group was found to be non-significant (t =1.61, p < 0.05).